Diminished muscle oxygen uptake and fatigue in spinal muscular atrophy. Issue 5 (31st March 2021) - Montes, Jacqueline; Goodwin, Ashley M.; McDermott, Michael P.; Uher, David; Hernandez, Feliz Marie; Coutts, Kayla; Cocchi, Julia; Hauschildt, Margarethe; Cornett, Kayla M.; Rao, Ashwini K.; Monani, Umrao R.; Ewing Garber, Carol; et al.
Abstract: Objective: To estimate muscle oxygen uptake and quantify fatigue during exercise in ambulatory individuals with spinal muscular atrophy (SMA) and healthy controls. Methods: Peak aerobic capacity (VO2peak ) and workload (Wpeak ) were measured by cardiopulmonary exercise test (CPET) in 19 ambulatory SMA patients and 16 healthy controls. Submaximal exercise (SME) at 40% Wpeak was performed for 10 minutes. Change in vastus lateralis deoxygenated hemoglobin, measured by near‐infrared spectroscopy, determined muscle oxygen uptake (ΔHHb) at rest and during CPET and SME. Dual energy X‐ray absorptiometry assessed fat‐free mass (FFM%). Fatigue was determined by percent change in workload or distance in the first compared to the last minute of SME (FatigueSME ) and six‐minute walk test (Fatigue6MWT ), respectively. Results: ΔHHb‐PEAK, ΔHHb‐SME, VO2peak, Wpeak, FFM%, and 6MWT distance were lower ( P < 0.001), and Fatigue6MWT and FatigueSME were higher ( P < 0.001) in SMA compared to controls. ΔHHb‐PEAK correlated with FFM% ( r = 0.50) and VO2peak ( r = 0.41) only in controls. Only in SMA, Fatigue6MWT was inversely correlated with Wpeak ( r = −0.69), and FatigueSME was inversely correlated with FFM% ( r = −0.55) and VO2peak ( r = −0.69). Interpretation: This study provides further support for muscle mitochondrial dysfunction in SMA patients. During exercise, we observed diminished muscle oxygen uptake but no correlation with aerobic capacity or body composition. We also observed increased fatigue which correlated with decreased aerobic capacity, workload, and body composition. Understanding the mechanisms underlying diminished muscle oxygen uptake and increased fatigue during exercise in SMA may identify additional therapeutic targets that rescue symptomatic patients and mitigate their residual disease burden.